Clinical, neurophysiological and neurochemical effects of non-invasive electrical brain stimulation in fibromyalgia syndrome—a systematic review and meta-analysis - Christine Winterholler; Maria Helena Coura; Pedro Montoya; Pedro Montoya (Frontiers in Pain Research)
BackgroundFibromyalgia syndrome (FMS) is linked to central sensitization and neuroplastic alterations that contribute to chronic pain, fatigue, cognitive, sleep, and affective disturbances. Conventional treatments offer limited benefit. Non-invasive transcranial electrical stimulation (tES), particularly transcranial direct current stimulation (tDCS), may modulate brain function and relieve symptoms, but findings remain inconsistent.ObjectiveTo systematically review and meta-analyze the effects of tES on clinical, neurophysiological, neuropsychological, and neurochemical outcomes in FMS.MethodsSeven databases were searched for studies published between April 2013 and April 2023. Eligible designs included randomized controlled trials, cross-over, one-arm, and case studies involving adult FMS patients. Data extraction followed Cochrane Collaboration guidelines and used RevMan 6.6.0.ResultsAnodal tDCS produced short- to mid-term reductions in pain and mood symptoms, especially when applied over M1 or DLPFC. Longer interventions and repeated sessions enhanced effects, though protocol heterogeneity limited comparability. Both subjective (VAS, NRS) and objective (QST) measures confirmed pain reduction. Cognitive improvements were inconsistent, and quality of life effects were limited. Neurophysiological and neurochemical changes suggested possible mechanisms, though findings varied. Study quality was mixed, with small sample sizes and methodological inconsistencies. Meta-analysis revealed statistically significant but small effects on pain (Hedges' g < 0.2), with limited evidence on clinical relevance.ConclusionsAnodal tDCS may offer short-term relief of pain and mood symptoms in FMS, potentially through modulation of cortical excitability and neuroplasticity. However, due to variability in findings and methodological limitations, its clinical relevance remains unclear. Future trials should use standardized protocols, assess long-term effects, and include clinically meaningful outcome measures.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023412332, PROSPERO CRD42023412332.